IMPLEMENTASI TRAFFICKING VICTIM PROTECTION ACT (TVPA) OLEH PEMERINTAHAN BARACK OBAMA DALAM MENANGANI HUMAN TRAFFICKING DI MEKSIKO TAHUN 2008-2012 - Hanifah, Ummu Ulfah; Utomo, Tri Cahyo; P, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Being a country located in a border with the United States (U.S.),Mexico had become a source and transit place for people who werevulnerable to human trafficking. The huge numbers of humantrafficking victims from Mexico in the U.S. enforced BarackObama’s governance made actions as efforts to cope the humantrafficking issue. The efforts that had been made by consideringTrafficking Victim Protection (TVPA) year 2000 with itsprosecution, protection, and prevention approach were givenmandate to the U.S. Department of State to evaluate and helpMexico. The objective of this study is to find out the efforts made bythe U.S. in combating the human trafficking in Mexico. Case studyand descriptive approach that were used had found out theimprovements in Mexico’s government efforts through reformationof the constitution, victim protection, and trafficking campaign asthe influence of the U.S. efforts.